Five Levels Conceptual Change: Perubahan Konseptual Siswa Melalui Model Learning Cycle 6E Pada Konsep Dinamika Rotasi - Anifatul Mardiyah; Tantri Mayasari; Farida Huriawati (Program Studi Pendidikan Fisika FKIP Universitas PGRI Palembang, 2020)
The learning process can be achieved when there is a change in students' understanding of concepts in a better direction. These changes can be realized by the existence of an alternative learning model. The purpose of this study was to analyze the conceptual changes experienced by students on the material of rotational dynamics through the learning cycle 6E learning model. This research is a type of qualitative research with a descriptive approach. The research results obtained are an increase in understanding of student concepts based on the results of the analysis of the pre-test post-test answers and student observation in carrying out learning. The tendency of students shows students A and B in the level of change is in complementation, students C and D are in construction, students E and F are in revision, and students G and H do not experience conceptual change or no conceptual change.